Investigating The Influence of Conformity and Fanaticism on Bullying Dynamics - Mulyana, Agus; Supenawinata, Anwar; Kurnia, Muhamad Fasha (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2023)
Bullying is a pervasive social issue within the Indonesian context, manifesting in various situations, including sports, where the behavior can occur between fellow athletes and supporters at a sporting event. Therefore, this research aimed to investigate the influence of conformity and fanaticism on incidents of bullying among supporters of the Persib Bandung football team. A quantitative causality approach was used, with data analysis executed through multiple regression to obtain 349 respondents. The results showed that conformity and fanaticism influenced bullying by Persib Bandung supporters. Specifically, the combined influence of the variables accounted for 3.3% of the observed incidents. Conformity had a partial influence of 15.8% on bullying ,while fanaticism did not show any statistically significant influence.